Novel Peptides Inhibit Zika NS2B-NS3 Serine Protease and Virus Replication in Human Hepatic Cell Line - Abdulrahman, Ammar Yasir; Khazali, Ahmad Suhail; Teoh, Teow Chong; Rothan, Hussin A.; Yusof, Rohana (Springer Verlag, 2019)
Zika virus (ZIKV) is a Flavivirus associated with several neurological complications. Currently, there are no vaccines or cures available and an efficient antiviral treatment is urgently needed to combat ZIKV infection. Herein, we targeted ZIKV NS2B-NS3 serine protease with short peptides to inhibit ZIKV replication in human hepatic cell line (WRL-68). The short peptide inhibitors were designed using Hyperchem 8.0.10 software. Docking energy and binding configuration were calculated using HADDOCK webserver. ZIKV NS2B-NS3 protease was produced as a recombinant single peptide in Escherichia coli and the protease activity was examined by measuring the cleavage of a fluorescent substrate in the presence of the peptides or aprotinin as a standard protease inhibitor. Computational analysis revealed that the short peptides, AYA2 and AYA9, exhibited lower docking energy to ZIKV protease than aprotinin. Both peptides also possessed lower half maximal inhibitory concentration (IC50), 30.9 and 22.1 µM respectively, against ZIKV protease activity when compared to aprotinin (35.4 µM). Interestingly, AYA2 and AYA9 exhibited minimal cytotoxic effects in WRL-68 cells and showed considerable inhibition against ZIKV replication in vitro at half maximal effective concentration (EC50) of 40.73 ± 2.3 µM and 34.65 ± 1.8 µM respectively. Fusion of these two peptides to MAP30 peptide substantially reduced the IC50 of ZIKV protease inhibition to 1.1 µM and inhibited ZIKV replication at EC50 of 0.5157 ± 0.03 µM. In sum, we reported novel peptides that effectively inhibited ZIKV replication in vitro. This study represents a cost-effective strategy of developing peptide inhibitors by shortening the peptides and producing them in recombinant form. © 2019, Springer Nature B.V.